The relationship between diaphragm muscle thickness, respiratory functions and respiratory muscle strength in athletes - Serhat Erail; Muhammet Hakan Mayda (Ozlem Book Center, 2023)
The aim of the study was to determine the relationship between diaphragmatic muscle thickness, respiratory function parameters and respiratory muscle strength in elite athlete groups. Cross-sectional method was used as research design. 58 male students (age= 20,14±2,71) studying at Yaşar Doğu Faculty of Sport Sciences participated in the study voluntarily. When analysed statistically; a positive significant difference was obtained between DiTeks and MEP. A higher positive significant difference was observed between DiTins and both MIP and MEP. In conclusion, this study showed that ultrasound imaging of the diaphragm is an important method to visualise many measurements and to obtain accurate results and that there is a relationship between diaphragmatic thickness and respiratory muscle strength and function parameters.